Pengaruh Pengembangan Ekowisata Bahari Terhadap Kehidupan Sosial dan Ekonomi Masyarakat Sekitar Pantai Batu Kalang Kenagarian Ampang Pulai Kecamatan Xi Tarusan Kabupaten Pesisir Selatan Provinsi Sumatera Barat - Rian Alfrianolta; Eni Yulinda; Viktor Amrifo (Berkala Perikanan Terubuk, 2016)
The research on the influence of marine ecotourism development towards social and economic life was held on December 20, 2015 until January 10, 2016 in South Pesisir regency of West Sumatra Province. This research aims to knowing the influence of marine ecotourism development towards life social and economic  and identifies the development done by government towards ecotourism. The method used was survey’s  method, the survey method done by observation, documentation and interview. The results of this research show that the influence of ecotourism development around communities Batu Kalang Beach was social disease arising from the development of ecotourism, and culture that does not change with the ecotourism and social processes that cooperation and mutual respect and mutual help among people, an influence on the life economic of the new employment for the community in the field of services and trade, the role of government in the development of attraction Batu Kalang Beach have done the planning, infrastructure development and make regulations for the convenience of visitors who come to Batu Kalang Beach.